Galaxy Zoo 1 : Data Release of Morphological Classifications for nearly 900,000 galaxies - Lintott, C; Schawinski, K; Bamford, S; Slosar, A; Land, K; Thomas, D; Edmondson, E; Masters, K; Nichol, R; Raddick, J; Szalay, A; Andreescu, D; et al. (2010)
Morphology is a powerful indicator of a galaxy's dynamical and merger history. It is strongly correlated with many physical parameters, including mass, star formation history and the distribution of mass. The Galaxy Zoo project collected simple morphological classifications of nearly 900,000 galaxies drawn from the Sloan Digital Sky Survey, contributed by hundreds of thousands of volunteers. This large number of classifications allows us to exclude classifier error, and measure the influence of subtle biases inherent in morphological classification. This paper presents the data collected by the project, alongside measures of classification accuracy and bias. The data are now publicly available and full catalogues can be downloaded in electronic format from http://data.galaxyzoo.org.